Evaluating Strategic Implications of Privatisation on Sensitive and Allied Government Organizations - Bokade, Milind (Digital Repository of Theses, 2025)
Privatization has been widely recognized as a mechanism for improving efficiency, reducing government expenditure, and fostering innovation. However, its application to sensitive and allied government organizations such as defence, intelligence, DAE, cybersecurity, space research, and critical infrastructure presents complex strategic implications. The transfer of control from public to private entities in these domains raises significant strategic concerns regarding national security, productivity, efficiency, data confidentiality, public accountability, and long-term sustainability. It is noted that there is significant lack of research on India that particularly determine strategic implications or consequences of privatisation of sensitive and allied organisations and integrity of India. In order to substantiate research, the viewpoints of expert’s government personnel, crucial stockholders who were neglected in earlier research have been included for analysing the privatisation of institutions given above. This study critically evaluates strategic implications of privatization on sensitive and allied government organisations in India with the risks and benefits. It presents sufficient empirical evidence that advocates the privatization of sensitive and allied government organisations The findings of study offers valuable inputs to the government or policymakers who are envisioning the privatization as a means of enhancing the overall efficiency specially in sensitive or strategic sectors with robust protective measures under legal institutional framework. The hypothesis-testing result gives insights to the relationship existing between privatization and major results associated with strategic governing parameters such as productivity, operational efficiency, and national security risks. The research fulfils research objective and corresponding research questions on strategic implications parameters. In conclusion, while privatization presents opportunities for enhancing efficiency and innovation in sensitive government sectors, its strategic implications necessitate careful evaluation. A balanced approach, incorporating rigorous governance measures and national security safeguards, are essential to ensure that privatization aligns with broader national interests while maintaining public confidence in essential services.